Analisis Financial Literacy dan Financial Attitude Terhadap Financial Management Behavior Dan Financial Satisfaction - Hikmah Hikmah; Triana Ananda Rustam (LPPM Universitas Putera Batam, 2022)
The financial aspect is one of the most important things to think about before starting a family since a family needs money to nurture and develop their family life; buying stocks, improving the quality of life, bringing children to school, and so on. Financial literacy has a very close relationship with financial management. Financial attitudes can be influenced by routine activities and the way a person works to see financial actions as good or bad by looking at his own perspective or the perspective of others; though, financial experience also contributes here. Therefore, without a good financial attitude, it will become a big difficulty in getting financial benefits for the future because these two factors are correlated to conquer short and long-term life goals. Financial Attitude and Financial Satisfaction The population in this study is the people of Batam City who have income. The number of samples is 204 respondents. The analysis tool used uses SEM with the SmartPLS 3.0 application. Questionnaire distribution is done through Google Form. The results of the study are that Financial literacy has a positive and significant effect on Financial Management Behavior in the people of Batam City, Financial Literacy has a significant effect on Financial satisfaction in the people of Batam City, Financial Attitude has a positive and significant effect on Financial management behavior in the people of Batam City, Financial Attitude has a positive effect. and significant to the financial satisfaction of the people of Batam City, Financial management behavior has an effect on the financial satisfaction of the people of Batam City